Mengukur Kepemimpinan Perempuan di Indonesia dengan Metode Fuzzy c-Means Clustering - Sukim Sukim; Firdaus Firdaus; Retnaningsih Retnaningsih; Efri Diah Utami (Program Studi Statistika Unisba, 2018)
Indonesia is fully committed to implement Sustainable Development Goals (SDGs). The goal 5 ofSDGs priorities the need to end discrimination against women and girls in all forms, and meetingtheir right to equal opportunities in employment, health and education. It is in line with thePresidential Instruction No. 9/2000 on gender mainstreaming in the National development programs.According to the result of the 2015 Intercensal Population census, about 49.75 percent of 255.18million Indonesian population are women. This large figure population of women could be an assetfor the national development in Indonesia when they are given the opportunity to advance andimprove their quality. Unfortunately, it is realized that there is still a gap between men and women inIndonesia due to limited access of women in education, employment, politics and high governmentalposition. Considering that women’s leadership is important to achieve and accelerate SDGs, thispaper aims to assess women’s leadership in Indonesia at province level by using 5 dimensions ofwomen’s leadership (politics, government, education, economy and decision making). Applying Fuzzyc-Means Clustering Method and 7 validity indexes, the result found that provinces in Indonesia canbe grouped into 4 clusters. The fourth cluster consists of 14 provinces and is considered as a clusterwith lowest women’s leadership.